2010
DOI: 10.1128/jcm.01505-09
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Genotype and In Vitro Susceptibilities of Cryptococcus gattii Strains from the Pacific Northwest of the United States

Abstract: Cryptococcus gattii emerged in North America in 1999 as a human and veterinary pathogen on Vancouver Island, British Columbia. The emergent subtype, VGIIa, and the closely related subtype VGIIb can now be found in the United States in Washington, Oregon, and California. We performed multilocus sequence typing and antifungal susceptibility testing on 43 isolates of C. gattii from human patients in Oregon, Washington, California, and Idaho. In contrast to Vancouver Island, VGIIa was the most frequent but not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
86
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 27 publications
9
86
1
1
Order By: Relevance
“…grubii isolates. This is in agreement with the results of Iqbal et al (2010) (Scholer & Polak, 1984), which is comparable to our results of 1.2 % (2/162) for clinical C. neoformans var. grubii isolates.…”
Section: Discussionsupporting
confidence: 94%
“…grubii isolates. This is in agreement with the results of Iqbal et al (2010) (Scholer & Polak, 1984), which is comparable to our results of 1.2 % (2/162) for clinical C. neoformans var. grubii isolates.…”
Section: Discussionsupporting
confidence: 94%
“…In Brazil, Souza et al [20] reported low MIC values for voriconazole and amphotericin B against isolates of C. gattii. It is worth highlighting that C. gattii VGIII was identified in this study and that the MIC values obtained for amphotericin B were low, in agreement with those in the literature [47,50,51], considering the cutoffs used by Nguyen and Yu [30] and Lozano-Chui et al [31]. For voriconazole, MIC values against C. gattii (range = 0.06 -0.5 mg/L were in agreement with those presented by Espinel-Ingroff et al [53], whereas against C. neoformans MIC values (range = 0.06-0.5 mg/L), were lower compared with those of the same study.…”
Section: Discussionsupporting
confidence: 78%
“…The majority of studies addressing in vitro susceptibility testing for amphotericin B against C. neoformans and C. gattii have shown that many of these isolates are susceptible at MIC values ≤ 1 mg/L [47,48,[50][51][52][53], similar to the MIC values obtained in this work. However, the literature reports MIC values for amphotericin B ≥ 1 µg/mL, such as Lozano-Chui et al [31], who reported MIC values of 3-4 mg/L, which were associated with treatment failure.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations